2013
DOI: 10.4161/jkst.23952
|View full text |Cite
|
Sign up to set email alerts
|

Egr2 and Egr3 are the unique regulators for systemic autoimmunity

Abstract: Systemic autoimmunity is characterized by widespread inflammation, autoantibody production and immune complex deposition. The regulatory mechanisms for the systemic autoimmunity are not fully understood. A paper by Li et al. revealed that Egr2 and Egr3, transcription factors required for T-cell anergy, are the regulators for systemic autoimmune disease. They showed evidence that Egr2 and Egr3 control cytokine productions and cell proliferation via SOCS and Batf regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…We also examined the mechanisms involved in pro-inflammatory phenotype conferred by Egr2 gene silencing in VSMC. Previous reports in myeloid cells showed that Egr2 induces suppressor of cytokine signaling-1 ( Socs1) and Socs 2, negative regulators of cytokine signaling, to inhibit inflammation 45, 46 . Because our RNA-seq data revealed downregulation of Socs 1 in db/dbVSMC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We also examined the mechanisms involved in pro-inflammatory phenotype conferred by Egr2 gene silencing in VSMC. Previous reports in myeloid cells showed that Egr2 induces suppressor of cytokine signaling-1 ( Socs1) and Socs 2, negative regulators of cytokine signaling, to inhibit inflammation 45, 46 . Because our RNA-seq data revealed downregulation of Socs 1 in db/dbVSMC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is noteworthy that Egr3 is also known to be important in the function of cells other than those of muscle cell type. Indeed, Egr3 can function in the development of neurons (Quach et al, ), activation of T‐cells (Safford et al, ; Sumitomo et al, ,) and vascular endothelial cells (Suehiro et al, ), and macrophage differentiation (Carter and Tourtellotte, ). In this regard, previous reports have described that muscle injury by CTX is neurotoxic (Harris, ).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated evidence has revealed the biological role of Egr3 in mammalian cells. Examples of some roles are activation and cytokine production in T‐cells (Safford et al, ; Sumitomo et al, ,), neuronal adaptation (O'Donovan et al, ), and transduction of growth signaling in endothelial cells (Suehiro et al, ). Moreover, Egr3 has been implicated in the proliferation of mammalian cells such as hematopoietic stem cells (Cheng et al, ) and T‐cells (Xi et al, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…EGR3 promotes the transformation of undifferentiated myotubes into intrafusal fiber [29]. EGR3 specifically induces the expression of TGF-β1 in CD4+ T cells and enhances the phosphorylation of STAT3 associated with TGF-β1 transcription [30]. That is to say, EGR3 is a transcription factor related to the expression of TGF-β1 and regulatory activity in humans.…”
Section: Discussionmentioning
confidence: 99%